2023
DOI: 10.1142/s021819672350025x
|View full text |Cite
|
Sign up to set email alerts
|

Finite groups satisfying the independence property

Abstract: We say that a finite group [Formula: see text] satisfies the independence property if, for every pair of distinct elements [Formula: see text] and [Formula: see text] of [Formula: see text], either [Formula: see text] is contained in a minimal generating set for [Formula: see text] or one of [Formula: see text] and [Formula: see text] is a power of the other. We give a complete classification of the finite groups with this property, and in particular prove that every such group is supersoluble. A key ingredien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…For Γ P and Γ E , these are the groups in which every element has prime power order; they were investigated by many authors, a summary of results can be found, for example, in [6,Theorem 1.7]. For Γ P and Γ ′ I , and for Γ E and Γ ′ R , they are determined in a recent paper by S. Freedman et al [7]. The remaining case is open.…”
mentioning
confidence: 99%
“…For Γ P and Γ E , these are the groups in which every element has prime power order; they were investigated by many authors, a summary of results can be found, for example, in [6,Theorem 1.7]. For Γ P and Γ ′ I , and for Γ E and Γ ′ R , they are determined in a recent paper by S. Freedman et al [7]. The remaining case is open.…”
mentioning
confidence: 99%